موقف الشريعة الاسلامية من الاستنساخ-دراسة فقهية مقارنة- - العقون, جميلة (University of Elouad, 2017)
يناقش هذا البحث موضوع الاستنساخ, الذي انتظم تنسيقه إلى ثلاث مباحث, فالمبحث الأول صدر بماهية الاستنساخ والذي انقسم إلى مطلبين, الأول أولج فيه حقيقة الاستنساخ ومرتكزاته, والثاني الفرق بين الاستنساخ وما قد يشتبه به, والمبحث الثاني أبرز فيه تاريخ الاستنساخ وأنواعه واستعمالاته, وقد قسم أيضا إلى مطلبين مطلب لتاريخ الاستنساخ الأدبي والعلمي, ومطلب لأنواع الاستنساخ واستعمالاته, أما المبحث الثالث أُدرج فيه حكم الاستنساخ بأنواعه الثلاثة ( النباتي, والحيواني, والبشري), وقد تناول أقوال وأدلة العلماء في كل نوع, ومن ثَم مناقشة بعض الأدلة التي تحتاج للمناقشة وصولا إلى الرأي الراجح وهو جواز استنساخ النبات والحيوان بشروط, وتحريم استنساخ الإنسان الحي والميت.discusses the topic of abrogation, which was divided to three chapters, the First one is about the conception of the abrogation which is itself divided into two parts. The first one about the truth and the bases of the abrogation, and the second part is about the abrogation and things alike, As for the second chapter is about the history of the abrogation and its kinds and uses, this chapter also was divided into two parts, the history of the literary and scientific abrogation, and the kinds of the abrogation and its uses, The third chapter is about the Islamic point of view towards the abrogation with all its three kinds in the Islamic Law, this chapter also covers some statements and evidences of the scientists in this case as they were separated between the acceptance and the denial of the abrogation, then discussing the evidences that need to be discussed all the way to the most accepted point of view which is the Permissibility of the abrogation of the plants and Animals and Prohibiting the abrogation on the human being either alive or dead.
مدكرة ماستر تخصص اصول الفقه
Keywords: : الاستنساخ، استنساخ نباتي، حيواني، البشري; Reproduction, plant, animal, human, reproduction